Quality Misallocation, Trade, and Regulations - Luca Macedoni; Ariel Weinberger (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Recent trade agreements have shifted their focus to non-tariff barriers such as regulations and product standards, which have been traditionally treated as pure domestic policies. The imposition of such standards reallocates production from small to large, high quality firms. We model regulations as a fixed cost that any firm selling to an economy must pay, consistent with stylized facts that we present. The fixed cost improves allocative efficiency, by reallocating production towards high-quality firms, who under-produce in the market allocation. Furthermore, the fixed cost generates a positive externality on the rest of the world as it induces entry of high-quality firms, but unilateral regulation lowers the terms of trade of the imposing country. The result justifies international cooperation based on the fact that such cooperation can improve welfare, rather than preventing negative consequences of tariff wars. We estimate our model and apply its gravity formulation to quantify the welfare consequences of imposing the optimal regulation, the extent of the positive externalities across countries, and the effects of cooperation.
Keywords: F12; F13; L11; 330; allocative efficiency; regulations; quality standards; variable markups; trade policy